Gamma nail™ in pertrochanteric fractures in elderly patients: is anatomical reduction necessary? A preliminary study - Calderazzi, Filippo; Pompili, Massimo; Carolla, Antonio; Schiavi, Paolo; Groppi, Giulia; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2015)
Aim of the work This study analyzes the clinical and radiographic results of 100 patients who underwent osteosynthesis with Gamma nail™, following fracture of the pertrochanteric region. Methods These patients were divided into 2 groups: A, those without anatomical reduction of the fracture and B, those with anatomical reduction. All patients were classified according to the ASA system, pre-injury and follow-up Harris Hip Score and pre-operative/post-operative radiographic evaluation. An univariate analysis has been performed comparing pre-injury and final follow-up Harris Hip Score. Moreover a multivariate analysis has been completed including: age, ASA classification, anticoagulant therapy, cognitive impairment, length of surgical procedure, type of surgical result, length of hospitalization, timing between trauma and surgical procedure. Results The univariate analysis documented no statistical significance (p=0.541). At multivariate analysis resulted as statistically significant only the age, the ASA classification and the timing between trauma and surgical procedure. Patients of group A have obtained rehabilitation time, fracture healing time and long-term functional results similar to patients of group B. Conclusions It is suggested that, compared with anatomic reduction, preoperative ASA, age and the time interval between trauma and surgery are more predictive criteria of patient mortality in the months following the intervention.